Analysis of the epidemiological transition of the population in the Lara state from 1950 to 2011 and its projection to 2020. (Revista Venezolana de Salud Pública, 2018)
The epidemiological transition is defined as the process of change in the patterns of mortality by causes and age groups in the population. With the aim to analyze the epidemiological transition in The State of Lara population in the period 1950-2011 and their projection until 2020, a longitudinal descriptive study of tendency was performed.
Keywords: Epidemiology; Demography; Epidemiological Transition